2019
DOI: 10.14742/ajet.3340
|View full text |Cite
|
Sign up to set email alerts
|

Saudi undergraduate students’ perceptions of the use of smartphone clicker apps on learning performance

Abstract: This study aimed to investigate how the use of a smartphone clicker app by a group of 390 Saudi Arabian male undergraduate students would impact their learning performance while participating in a computer science class. The smartphone clicker app was used by the students during peer group discussions and to respond to teacher questions. A conceptual framework identified teacher-student and student-student interactions, collaborative learning, and student engagement as three primary practices that could improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…small screen, small keyboard, limited data storage, limited battery life, etc. ), reluctance to use smartphones for learning, learners' distraction, or teachers' willingness and readiness to employ these devices as educational tools (Aljaloud, et. al., 2019;Ismail, et.…”
Section: Literature Reviewmentioning
confidence: 99%
“…small screen, small keyboard, limited data storage, limited battery life, etc. ), reluctance to use smartphones for learning, learners' distraction, or teachers' willingness and readiness to employ these devices as educational tools (Aljaloud, et. al., 2019;Ismail, et.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies showed decreased hesitation in asking via‐system questions (Shimaya et al, 2020) when using question‐support systems such as Clicker (Aljaloud et al, 2019; Egelandsdal et al, 2019; Lantz & Stawiski, 2014; Mayer et al, 2009) or other more complex input methods (Damanik, 2020; Nitza & Roman, 2016; Scornavacca et al, 2009). Similarly, Twitter (Tang & Hew, 2017) or chat channels (Tuhkala & Kärkkäinen, 2018) were also found to promote online student–lecturer interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that audience response systems such as Clicker promote the active participation of students by providing another means of asking questions or presenting ideas (Aljaloud, Gromik, Kwan, & Billingsley, 2019; Egelandsdal, Ludvigsen, & Ness, 2019; Lantz & Stawiski, 2014; Mayer et al, 2009). A previous study suggested that the anonymity provided by Clicker enhanced student participation during lectures (Freeman, Blayney, & Ginns, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies in the last few years have focused on students' perceptions of learning in science. We have identified different data collection strategies in this regard, such as interviews (Roberts et al, 2018), reflection forms completed by students (Roberts et al, 2018), questionnaires (Jones, 2017;Sample McMeeking et al, 2016) and Likert-scale items (Aljaloud et al, 2019;Jeong et al, 2016), which seem to be the most promising strategy. For example, to study students' perceptions of learning in a science classroom, Jeong, González-Gómez, & Cañada-Cañada (2016, p. 751) used five-point Likert-scale items (e.g., "The instruction methodology used in this course helped me to understand easily scientific contents"; "The course as a whole was a valuable learning experience"), and in research aiming to understand how a smartphone clicker app can impact learning performance in a computer science class, Aljaloud et al (2019, p. 91) developed an online survey with Likert-scale items to measure students' perceptions of their learning performance (e.g., "Using the smartphone clicker app helped to improve my ability to comprehend the concepts in this module").…”
Section: Perception Of Learningmentioning
confidence: 99%